Quantitation of olefins in sustainable aviation fuel intermediates using principal component analysis coupled with vacuum ultraviolet spectroscopy - Kosir, Shane; Feldhausen, John; Bell, David; Cronin, Dylan; Boehm, Randall; Heyne, Joshua (Frontiers in Fuels, 2023)
Olefins, a common intermediate from biomass conversion processes, are undesirable in jet fuel because of their poor thermal stability. This paper presents an approach for olefin quantitation using 2D gas chromatography coupled with vacuum ultraviolet spectroscopy. Principal component analysis is was used to reduce the dimensionality of the spectroscopy data from a highly olefinic fuel intermediate and enable olefin screening and quantitation. A vacuum ultravioletprincipal component template was created that enables enabled olefin screening quantitation, without the use of a GCxGC template. Principal component olefin quantitation was performed andwhich was compared to the existing GCxGC-VUV approach from the literature. The principal component method was able to identify and quantify trace amounts of cyclodienes, which represents an improvement relative to the GCxGC templatewhich were present at only 0.01 wt% in the fuel sample. The principal component approach also identifies species that fall outside of the GCxGC template. For instance, quantitation with GCxGC resulted in an olefin concentration of 0.95 times that of the principal component method due to olefins falling outside of unexpected GCxGC regions. It is proposed that principal component quantitation can supplement the existing GCxGC-VUV olefin quantitation method. The principal component results were compared with 13C and 1H NMR data for further validation, which confirmed that the fuel had a high concentration of olefins and alkanes with little aromatic content.